A Highly Sensitive Time-Gated Fluorescence Immunoassay Platform Using Mn-Doped AgZnInS/ZnS Nanocrystals as Signal Transducers - Gallian, Brandon; Zaeimian, Masoumeh Saber; Hau, Derrick; AuCoin, David; Zhu, Xiaoshan (Frontiers in Physics, 2021)
In this work, a time-gated immunoassay platform using low-energy excitable and fluorescence long-lived Mn:AgZnInS/ZnS nanocrystals as signal transducers was developed and applied to the detection of the capsular polysaccharide (CPS) of Burkholderia pseudomallei, a Gram-negative bacterium that is the causative agent of melioidosis. CPS is a high molecular weight antigen displayed and is shed from the outer membrane of B. pseudomallei. The immunoassay using the time-gated platform presents a limit of detection at around 23 pg/ml when CPS is spiked in human serum.